Students' Mathematical Understanding Ability and Self-Confidence Through Collaborative Think Pair Share and Talking Stick Learning Models at SMA Kemala Bhayangkari-2 Rantau Prapat - Magriani Nasution, Dina; Harahap, Amin (International Journal of Educational Research & Social Sciences, 2023)
Through the combination of the Think-Pair-Share and Talking-Stick models, this project aimed to improve learning outcomes and increase mathematical engagement among students in class XI at SMA Kemala Bhayangkari-2 Rantau Prapat. This study represents classroom action research. The research was done in two cycles, with each cycle including preparation, execution, observation, and reflection. This study involved 30 students from class XI at SMA Kemala Bhayangkari-2 Rantau Prapat. The sources of data are teachers and students. Various methods of data collecting include observation, interviews, testing, and document analysis. Using data triangulation and triangulation procedures to determine the veracity of the data. Comparative and critical descriptive analysis approaches were employed in the data analysis. Planning, implementation, observation and interpretation, and analysis and reflection are the research methods. The results demonstrated that by applying the Think Pair Share collaborative approach with the Talking Stick, learning outcomes may be enhanced and student engagement encouraged. This study concludes that the implementation of the Think Pair Share Model Collaboration with the Talking Stick model can improve learning results and stimulate student participation in administration courses.